2021
DOI: 10.47021/0320-3557-2021-113-119
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Indices of Blood Serum of Rubella-Resistant Carp Breed at the End of the Feeding Period

Abstract: Biochemical parameters of blood serum in resistant and susceptible to rubella pathogens groups of carp at the end of the feeding period are studied. The material was taken from 6 individuals of the Angelina scaly rubella-resistant breed kept at the experimental pond base "Sunoga" of the Papanin Institute for Biology of Inland Waters RAS, Yaroslavl oblast. For comparison, we used same-age carps from the fish farm "Kirya", Chuvash Republic, susceptible to rubella pathogens: 8 specimens of scaly and 8 mirror carp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study of the indices of nonspecific immunity in rubella-resistant carp will make it possible to understand the mechanisms that ensure the immunity of fish to infectious diseases. Previously, the authors have shown differences in some immunobiochemical parameters between rubella-resistant carp and breeds susceptible to disease (Mikryakov et al, 2019a(Mikryakov et al, , 2019bSuvorova et al, 2019). It was found that individuals of the rubellaresistant breed differ from carp of other breeding groups in the proportions of the content of various forms of leukocytes; the intensity of leukopoiesis; the level of protein, glucose, and total lipids; oxidative processes; and antioxidant protection.…”
Section: Short Communicationsmentioning
confidence: 99%
“…The study of the indices of nonspecific immunity in rubella-resistant carp will make it possible to understand the mechanisms that ensure the immunity of fish to infectious diseases. Previously, the authors have shown differences in some immunobiochemical parameters between rubella-resistant carp and breeds susceptible to disease (Mikryakov et al, 2019a(Mikryakov et al, , 2019bSuvorova et al, 2019). It was found that individuals of the rubellaresistant breed differ from carp of other breeding groups in the proportions of the content of various forms of leukocytes; the intensity of leukopoiesis; the level of protein, glucose, and total lipids; oxidative processes; and antioxidant protection.…”
Section: Short Communicationsmentioning
confidence: 99%